Correlation of intra partum electronic fetal monitoring with neonatal outcome - C., Sunitha; Rao, P. S.; S., Prajwal; Bhat, Reema Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The importance of fetal monitoring during labour has been realized since long. The stress of uterine contractions may affect the fetus adversely especially if the fetus is already compromised, when the placental reserves are suboptimal, or when cord undergoes compression as in those associated with diminished liquor amnii or iatrogenic uterine hyperstimulation due to injudicious use of oxytocin. Even a fetus which is apparently normal in the antenatal period may develop distress during labour. Hence fetal monitoring during antepartum and intrapartum periods is of vital importance for timely detection of fetal distress so that appropriate management may be offered. Methods: This study was a prospective observational study included 100 patients of more than 34 weeks period of gestation were divided into two groups. Patients in labour were analyzed on an Electronic Monitor. Delivery conducted was either by vaginal route, instrumental or by caesarean section depending upon the fetal heart rate tracings and their interpretations as per the case. At the time of delivery umbilical cord blood was taken for the pH analysis. All new born babies were seen by the paediatrician immediately after the delivery and 1 and 5 minute APGAR score assessed for the delivered baby. The various EFM Patterns obtained were compared with the neonatal status at birth using the parameters already mentioned. The false positives and false negatives if any were tabulated. Data so obtained was analyzed statistically thereafter. Statistical Package for Social Sciences (SPSS) Version 13.0 was used for the purpose of analysis. Results: Results revealed that among the 50 subjects of the case group, 7 subjects showed the absence of the beat to beat variability, 12 subjects showed early deceleration, 32 subjects showed late deceleration, and 6 subjects showed the presence of variable deceleration. No significant association of beat to beat variability, early and variable deceleration could be established with meconium staining/NICU admissions/low APGAR. A significant positive association between persistent late deceleration with MSL, APGAR <7 at 1 min, and Instrumental/LSCS delivery was seen. A significant positive association between any CTG abnormality and APGAR at 1 min, type of delivery, and meconium staining was seen. Conclusions: EFM should be used judiciously. Cardiotocography machines are certainly required in the labour room. Equally important is the proper interpretation of the CTG tracings so that unjustified caesarean sections can be minimized, at the same time picking up cases of fetal distress in time which is likely to improve fetal outcome.